Elemental composition of household dusts extracted in simulated body fluids and their impact on culturable pathogenic bacteria responses - Baysal, Aslı; Zora, Sevilay; Saygın, Hasan (Springer, 2024)
In the last decade, a great deal of research has focused on the determination of potential toxic elements by total concentration and identification the microorganisms in dust. However, determining bio-relevant (e.g., inhalable) forms of elements instead of total contents in acids is necessary for human health. Moreover, examination of the behavior of microorganism under these bio-relevant conditions and revealing the interaction between elements and pathogens is vital and necessary for deeper understanding. However, previous studies have ignored these topics. Therefore, the present study aimed to (i) investigate elements in household dusts extracted in simulated lung fluids, (ii) examine the total concentration of culturable bacteria and their biochemical responses with exposure to bio-fractions of household dusts, and (iii) assess their relations and risks using the model approaches by inhalation. Here, settled dusts were collected in 25 houses, and extracted in four simulated body fluids to determine bio-fractions of elements. Moreover, total count of potentially pathogenic and heterotrophic bacteria, and four clinically important culturable pathogens were incubated in the presence of household-dusts extracted in simulated body fluids. The activity, biofilm, biochemical and oxidative responses of pathogens were measured following household-dust exposures. Afterward, the relationship between elements and pathogen responses were evaluated, and model and derived approaches were used for risk assessments of elements and pathogens. The higher daily intake of elements obtained in artificial lysosomal fluid fraction of household dust mimicking the inflammatory condition compared to other body fluids. Moreover, bacterial responses were mainly influenced from bio-fractions of household dusts and their elemental contents.
Keywords: metals; settled indoor dust; microorganism